Influence of Ketamine on Early Postoperative Cognitive Function After Orthopedic Surgery in Elderly Patients - Lee, Ki Hwa (Anesth Pain Med, 2015)
BACKGROUND: Postoperative cognitive dysfunction (POCD) is a serious and frequent complication after surgery, especially in elderly patients. Ketamine is an N-methyl D-aspartic acid receptor antagonist with demonstrated neuroprotective effects. An intravenous bolus of a sub-anesthetic dose (0.5 mg/kg) of ketamine can reduce postoperative delirium (POD) and POCD after cardiac surgery. But, the influence of ketamine on early POCD after non-cardiac surgery is unclear. OBJECTIVES: The current study aimed to evaluate the influence of ketamine on early postoperative cognitive function after orthopedic surgery in elderly patients. PATIENTS AND METHODS: Fifty six elderly patients (> 60-years-old), scheduled for elective orthopedic surgery during general anesthesia (duration of anesthesia > two hours) were enrolled. Patients received intravenous bolus, a total of 3 mL mixed with 0.9% normal saline and 0.5 mg/kg ketamine (K group) or 3 mL of 0.9% normal saline (N group). Three neurocognitive function tests (mini-mental status examination, trail-making test, digit substitution test), and c-reactive protein (CRP) concentration were determined before surgery and on postoperative day one (POD 1) and postoperative day six (POD 6). RESULTS: The two groups had similar demographic characteristics except for the gender. Surgical and anesthetic data were not significantly different. A statistically significant difference was observed in comparison of trail-making test score. Trail-making test score increased more in the N group (52.5 points) than the K group (13 points) at POD 1 (P = 0.047) compared with baseline scores. There were no significant differences in the mini-mental status examination, digit substitution test and CRP concentration at POD 1 and POD 6 between the two groups. POCD (the two Z-scores in more than two tests or the combined Z-score was 1.96 or more) was present in one patient (4%) in the K group at POD 6 (P = 0.98). CONCLUSIONS: The incidence of POCD was not significantly influenced by a bolus dose of ketamine (0.5 mg/kg) after orthopedic surgery in elderly patients. There were no negative effects of ketamine on early POCD.